Characterization of organic matter degradation during composting of manure–straw mixtures spiked with tetracyclines - Hu, Zhenhu; Liu, Yuanlu; Chen, Guowei; Gui, Xianyang; Chen, Tianhu; Zhan, Xinmin (Bioresource technology, 2011)
► We investigated humification and mineralization of organic wastes during composting. ► More than 93% of tetracyclines was degraded during a 45-day composting. ► XRD spectra confirmed the natural formation of struvite during composting. ► Control the ammonia loss and fix soluble phosphorus during composting. The objective of this study was to investigate humification and mineralization of manure–straw mixtures contaminated by tetracyclines during composting. Hen manure, pig manure and rice straw were used as the raw materials. The manure–straw mixtures were spiked with tetracycline, chlortetracycline, and oxytetracycline at the concentration of 60mg/kg dry matter. The results show that tetracyclines had no obvious influence on the composting process and more than 93% of the tetracyclines was decreased during a 45-day composting. The Fourier transform infrared (FTIR) spectra indicated that easily biodegradable components such as aliphatic substrates, carbohydrates and polysaccharides were decomposed and the contents of aromatic components relatively rose during the composting. The X-ray diffraction (XRD) spectra confirmed the natural formation of struvite, the degradation of easily biodegradable components, and the mineralization of organic matter during the composting. Therefore, FTIR and XRD analysis can be useful tools for monitoring the composting process.